Attention modulation during motor preparation in Parkinsonian freezers: A time–frequency EEG study. Issue 12 (December 2016) - Tard, Céline; Dujardin, Kathy; Bourriez, Jean-Louis; Molaee-Ardekani, Behnam; Derambure, Philippe; Defebvre, Luc; Delval, Arnaud
Highlights: EEG oscillations can be studied during attentional processes and motor preparation. Parkinsonian patients with freezing of gait did not display beta desynchronization. Post-discrimination processing was impaired in parkinsonian patients with freezing of gait. Abstract: Objective: To investigate the cortical integration of attentional stimuli during motor preparation in parkinsonian patients with freezing of gait (FoG, n = 12) or without freezing of gait ( n = 13), and in aged-matched healthy controls ( n = 13). We hypothesized that interference between attention and action in freezers would be revealed by differences in cortical modulation during this dual task. Methods: Attention during step preparation was modulated by means of an auditory oddball discrimination task. EEG oscillations in different frequency bands were measured for the attentional stimulus and the motor stimulus. Results: Over the 500 ms following the sound, low-frequency power increased in all three groups. This was followed by a power decrease in mid-range frequencies after both target and standard sounds in the healthy controls and in the non-FoG group. In contrast, EEG oscillations in the beta band were impaired in the FoG group, who notably failed to display event-related desynchronization after perceiving the sound. Conclusions: An attentional stimulus was able to trigger event-related desynchronization before motor preparation in the non-FoG group but not in the FoG group. Significance: In the FoG group, stimulus discrimination was maintained but the coupling between attention and motor preparation was impaired.